PERCEPTIONS OF HUMAN-NATURE RELATIONSHIPS IN JOY HARJO'S AMERICAN INDIAN POEMS - Wijaya, Silvia Marta; Rahayu, Masnia (Universitas Islam Sumatera Utara, 2024)
The connection between nature and Joy Harjo's American Indian poems is worth discussing because nature impacts human existence. To confirm and consider ideas about the environment, particularly the environment's vulnerability to human activity and exploitation, this study examines metaphorical language in some of Harjo's works. By examining the complex interactions between the environment and humans, this study advances our knowledge of how issues of ecology are portrayed in literature to promote environmental awareness. This research examines ecological themes in two American Indian poems by Joy Harjo, Talking with the Sun and Once the World Was Perfect, using Garrard's ecocritical theory and qualitative methodology. The research shows how Harjo's works demonstrate the detrimental effects of human activities on ecosystems and, as a result, criticize anthropocentrism through qualitative ecocritical analysis. Talking with the Sun explores the spiritual bond between humans and nature, while Once the World Was Perfect highlights the damages caused by environmental degradation and human exploitation. This research contributed to the discourse of ecocriticism by highlighting how literature can highlight issues of the environment.